Recreational games in the promotion of physical capacities during physical education class - Ortiz-Zorrilla, Freddy (2023)
The objective of this study was to develop conditional physical abilities such as strength and speed in order to improve the physical condition of students, motivating them to perform any type of activity that involves personal movement for fun. The game was the fundamental piece to carry out this research, where a quantitative approach was used and the type of research was quantitative observation with a descriptive approach based on the figures used; The instrument used was the physical aptitude test granted by INEFI, this measures conditional physical abilities and also uses height and weight, together with age to measure the person's BMI. The results suggest that if children have difficulty developing the physical abilities of strength and speed, but through recreational play, it can be improved. As conclusions, the study shows that recreational games are an effective strategy to improve physical abilities, such as strength and speed, in boys and girls. Through playful and fun activities, children can develop their physical potential in a motivating and stimulating way. In addition, the game enriches the student in the cognitive, social, family and cultural fields, because they allow even the girls who are the least motivated when it comes to physical activity to be the first to participate.